MANAJEMEN KESEHATAN KUDA PEJANTAN HANOMAN YR DI PETERNAKAN KUDA TOMBO ATI STABLE SALATIGA - , FERA DWI ARYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This on the job training held on March, 2-9th 2014 at Tombo Ati Stable horse ranch addressed in Gintungan village, Butuh, Tengaran, Semarang, Central Java. There are 57 horses consists of 3 male, 23 female, 15 belo above 1 year, 6 belo under 1 year and 10 race horse. Data obtained from interview result with stable officer, direct observation, data gaining and following the on the job training regulation such as preparation of stable tools and stable place, clean the stable include the feeding and drinking place from feses, prepare the horse feed, feed the horses, take care the horses by do the grooming and exercise everyday. Based on the job training concluded that everything are done well. Start from sanitation and stable care every morning and afternoon, so do the grooming and exercise. Treatment before and after marriage, feeding is fulfilled by well nutrition, vitamins is given routinely that can minimize the disease. The disease that usually come on ranch like wounds, trombus and influenza. Direct medical treatment done quickly due to the ranch has its own private vets.